Financial Performance Assessment of PT Pelabuhan Indonesia II (Persero) in Comparison with other Port Companies Locally and Globally - Okitanya, Rininta Rizkia; Soekarno, Subiakto (Journal of Business and Management, 2012)
Two-thirds of Indonesia is water. Thousands lined the island of Sabang to Merauke. As an archipelago, marine transportation plays an important role in the development of Indonesia. Supported by Indonesia's strategic location as it is situated at the crossroads of world trade routes. Therefore it required sea transportation system that is reliable and efficient. This can be achieved if the management of the navy, both shipping companies and port operator operates properly and professionally.This study focuses on the performance of the port operator, PT Pelabuhan Indonesia II, which has its head office in Jakarta. PT Indonesia II port operational areas of the company covers 10 provinces and it has three subsidiaries, affiliate one, two business units and one joint operation.The performance that discussed in this study focused on financial performance, since only a company with good financial performance that can perform the operations well too.This final will discuss the performance of PT Pe4labuhan Indonesia II and will also be compared with other companies in the same industry both locally and globally. The author will use some framework. In the end, come to the conclusion and recommendation for PT Pelabuhan Indonesia II to achieve better performance.As a conclusion, PT Pelabuhan Indonesia II almost rivaling global competition a leader in several assessment framework, with an optimal capital structure when the WACC minimized at 53% of debt and 47% of equity while the maximum of firm value of IDR 8,620,465,240,669.Keywords: Archipelago, Port, Performance, Comparison, Financial statements analysis.